The burden of brain and central nervous system cancers in Asia from 1990 to 2019 and its predicted level in the next twenty-five years - Xin Liu; Lin-Can Cheng; Teng-Yu Gao; Jie Luo; Chao Zhang (BMC, 2023)
Abstract Background Primary brain and central nervous system cancer (collectively called CNS cancers) cause a significant burden to society. The purpose of this study was to evaluate the trends in the burden of CNS cancers from 1990 to 2019 and to predict the incidence and mortality rates and the corresponding numbers for the next 25 years to help countries to understand the trends in its incidence and mortality, and to make better adjustments or formulation of policies and allocation of resources thereby reducing the burden of the disease. Methods The 2019 Global Burden of Disease Study provided incidence rates, death rates, and disability-adjusted life year (DALY) data in Asia from 1990 to 2019. To reflect the trends in the age-standardized incidence, mortality, and DALY rates, the estimated annual percentage change (EAPC) was determined. The Bayesian age-period cohort (BAPC) model was employed to predict the burden of CNS cancers in the next 25 years. Results The incidence, death, and DALY rates of CNS cancers all increased from 1990 to 2019. The age-standardized incidence rate (ASIR) for CNS cancers increased from 9.89/100,000 in 1990 to 12.14/100,000 in 2019, with an EAPC of 0.69 (95% confidence interval (CI): 0.65, 0.73). The ASDR and the age-standardized DALY rate both decreased, with EAPCs of − 0.08 and − 0.52, respectively. Before 2005, the age-standardized DALY rate in East Asia was much greater in females than in males, while in Central Asia, the age-standardized death and DALY rates in males both increased sharply after 2000. In contrast to 1990, the caseload increased for the 55-70 years age group. The number of deaths decreased sharply among individuals aged younger than 20 years, especially in East Asia, accounting for only 5.41% of all deaths. The age group with the highest mortality rate was > 60 years, especially in Japan. The ASIR will continue to increase in Asia from 2020 to 2044, and the ASDR will gradually diminish. The incidence and number of deaths from CNS cancers in Asia are expected to increase over the next 25 years, especially among females. Conclusions The study identified an increasing trend in morbidity, mortality and disability-adjusted life-years (DALYs), with differences in age-standardized morbidity rates for different population groups. In addition, it is noteworthy that the burden of disease (as measured by disability-adjusted life-years (DALYs)) is higher among women in Central Asia compared with other regions. ASIR will continue to increase over the next 25 years, with the increase in female cases and mortality expected to be more pronounced. This may need to be further substantiated by additional research, on the basis of which health authorities and policymakers can better utilize limited resources and develop appropriate policies and preventive measures.